(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1994)
A Late Triassic conodont fauna is described and illustrated for the first time from the San Cassiano Formation of the eastern Dolomites (Tamarin). The co-occurrence of Metapolygnathus auriformis, M. carnicus, M. baloghi, M. polygnathiformis, Gladigondolella tethydis, Gl. arcuata and Gl. malayensis malayensis indicates a Late Julian age. The fauna corresponds to the auriformis Zone (Austriacum Zone according to ammonoid zones). This pelagic conodont fauna, characteristic of relatively deep water, shows strong faunal affinities with coeval faunas from European Tethyan regions(mainly Greece, Turkey, NE Hungary, and Alps) and northern Kumaun region of Tethys Himalaya.